Animal experimental models in the study of nutrition - González Santiesteban, Aimé; Velazco Brito, Lázaro; González Barrera, Yuneysi (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Nutrition is a biological expression of the harmonious integration of all the systems present in the body. The impetuous development of science and the progress in the successful treatment of pathologies with high morbidity and mortality, demonstrates the necessary use and development of clinical trials prior to the use of new therapeutic proposals. For ethical reasons, these tests are preceded by research in experimental models of laboratory animals, which is why the validation of these models that allow progress in these studies in humans acquires greater interest every day. Objective: Describe the essential aspects in the design and analysis of experimental models carried out in the study of nutrition. Methods: A systematic bibliographic review was carried out to describe the experimental models carried out in the study of nutrition, where theses were considered to opt for the title of 1st Degree specialist in Normal and Pathological Physiology, as well as original and review articles published between 2013 and 2023 in English and Spanish. The search was carried out in the SciELO and Google Scholar databases in September 2023. Development: Several models of malnutrition produced by different causes and of nutritional recovery have been developed, which have served in the research of therapeutic proposals. Conclusions: The use of the experimental models designed allowed us to know the alterations produced in the nutritional status in the different malnutrition and recovery schemes as well as the response of applied therapeutic principles.